I can't seem to get any kind of result which I find useful when I use the fact that $$\int_0^af(x)\,\mathrm dx=\int_0^af(a-x)\,\mathrm dx$$

After using trigonometry, I end up getting: $$\int_0^{\pi}\frac{(\pi-x)\sin x}{1+\cos^2x}\,\mathrm dx$$

I don't see how this is useful. Please help.

  • $\begingroup$ hint: add both the integral in the body of your post and the one in the title. $\endgroup$ – abel Dec 13 '14 at 0:23

It follows from what you've done so far that

$$2 \int_0^\pi \frac{x \sin x}{1+\cos^2 x} dx = \int_0^\pi \frac{\pi\sin x}{1+\cos^2 x} dx$$

The integral on the left is twice the one you're after. The integral on the right can be evaluated using the 'obvious' substitution of $u = \cos x$ and then hopefully you recognize the integral.

Added (in response to comment below)

You have shown that

$$\int_0^\pi \frac{x \sin x}{1+\cos^2 x} dx = \int_0^\pi \frac{(\pi - x) \sin x}{1+\cos^2 x} dx $$

In other words,

$$\int_0^\pi \frac{x \sin x}{1+\cos^2 x} dx = \int_0^\pi \frac{\pi \sin x}{1+\cos^2 x} dx - \int_0^\pi \frac{x\sin x}{1+\cos^2 x} dx $$

and hence

$$2 \int_0^\pi \frac{x \sin x}{1+\cos^2 x} dx = \int_0^\pi \frac{\pi\sin x}{1+\cos^2 x} dx$$

So we can write the original integral as being equal to this integral:

$$ \int_0^\pi \frac{x \sin x}{1+\cos^2 x} dx = \frac{\pi}{2} \int_0^\pi \frac{\sin x}{1+\cos^2 x} dx$$

Clear now?

  • $\begingroup$ $\sin x$ missing in your integrand? $\endgroup$ – abel Dec 13 '14 at 0:24
  • $\begingroup$ Why is it twice the one i'm after? Did you use the f(x)=f(a-x) equation? I don't follow your working $\endgroup$ – RobChem Dec 13 '14 at 10:49
  • $\begingroup$ I've added working above. $\endgroup$ – Simon S Dec 13 '14 at 12:22

$\color{red}{\hat{I}=\displaystyle\int_{0}^\pi\dfrac{x\sin x}{1+\cos^2x}dx}=\color{blue}{\displaystyle\int_{0}^\pi\dfrac{(\pi-x)\sin x}{1+\cos^2x}dx=\hat{I}}$

$\therefore 2\hat{I}=\color{red}{\hat{I}}+\color{blue}{\hat{I}}=\color{green}{\pi\displaystyle\int_{0}^\pi\dfrac{\sin x}{1+\cos^2x}dx}$

$I=\displaystyle\int\dfrac{\sin x}{1+\cos^2x}dx=\displaystyle\int\dfrac{\sec x\tan x}{\sec^2x+1}dx$

$\therefore\sec x=z \implies \displaystyle\int\dfrac{\sec x\tan x}{\sec^2x+1}dx=\displaystyle\int\dfrac{dz}{z^2+1}$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.